​​Exploring Key Elements and Effective Strategies for Establishing Long-Term B2B Customer- and Partner Relationships​: Master Thesis - Päivärinta, Mikael Henrikki (My University, 2024)
What is the role of long-term successful customer and partner relationships in business and how are they formed? What is the role of salesperson in creating long-term relationships and what do they do in practice? This research shows the importance of building long-term relationships with customers and partners. Successful customer and partner relationships are vital in the modern-day business environment. Companies are seeking competitive advantage continuously and having loyal customers and partners who are committed to mutual success is vital for companies. This is why it is necessary to understand the factors, which are the key in the relationship building process. Salespeople are in the forefront of customer and partner relationship building and that is why the way they act stands out strongly and plays a significant role in successful rela-tionships. The goal of this research was to identify the key elements in the activities and character of sellers that allow long-term relationships to be established. The objectives of this research were to increase awareness in the business how the relationships are created and what kind of strategies salespeople use in the creation process. The method used in this research was qualitative method. To this research salespeople from the case organization was interviewed. Interview questions were created based on the re-search goal and objectives. The research findings support previous research findings around this topic. Salespeople are in the critical role in relationship building. Individual characteristics and strategies they use in relationship building have major role how successful the relationship eventually is. This is why it is also important to focus on training and supporting salespeople especially during the relationship building phase. Mikä on pitkäaikaisten onnistuneiden asiakas- ja kumppanisuhteiden rooli liiketoiminnassa ja miten ne muodostuvat? Mikä on myyjän rooli pitkäaikaisten suhteiden luomisessa ja mitä he tekevät käytännössä? Tämä tutkimus osoittaa pitkäaikaisten asiakas- ja kumppanisuhteiden rakentamisen tärkey-den. Onnistuneet asiakas- ja kumppanisuhteet ovat elintärkeitä nykypäivän liiketoimintaym-päristössä. Yritykset etsivät jatkuvasti kilpailuetua, ja uskolliset asiakkaat ja kumppanit, jotka ovat sitoutuneet yhteiseen menestykseen, ovat yrityksille elintärkeitä. Siksi on välttämätöntä ymmärtää tekijät, jotka ovat avainasemassa suhteen rakentamisprosessissa. Myyjät ovat eturintamassa asiakas- ja kumppanisuhteiden rakentamisessa, ja siksi heidän toimintatapan-sa korostuvat ja näyttelevät merkittävää roolia onnistuneissa suhteissa. Tutkimuksen tavoitteena oli tunnistaa keskeiset tekijät myyjien toiminnassa ja luonteessa, jotka mahdollistavat pitkäaikaisten suhteiden luomisen. Tutkimuksen tavoitteena oli lisätä tietoisuutta liiketoiminnassa siitä, miten suhteet luodaan ja millaisia strategioita myyjät käyt-tävät luomisprosessissa. Tutkimuksessa käytettiin laadullista menetelmää. Tutkimusta varten haastateltiin tapausor-ganisaation myyjiä. Haastattelukysymykset luotiin tutkimuksen tavoitteen ja tavoitteiden pohjalta. Tutkimustulokset tukevat aiempia tutkimustuloksia tästä aiheesta. Myyjät ovat kriittisessä roolissa suhteiden rakentamisessa. Yksilölliset ominaisuudet ja strategiat, joita he käyttävät suhteiden rakentamisessa, vaikuttavat merkittävästi siihen, kuinka onnistunut suhde lopulta on. Siksi on myös tärkeää keskittyä myyjien koulutukseen ja tukemiseen erityisesti suhteen rakentamisvaiheessa.
Keywords: customer relationship management; relationship marketing; trust; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management; Tuotantotalous